Relation of neutrophil-to-lymphocyte ratio with coronary artery disease severity in patients undergoing coronary angiography - Nepal, Bikash; GHimire, Jeet P.; Karki, Biplave; Mahaseth, Aditya; Uranw, Surendra; Pandey, Naveen Kumar; Shah, Prashant; Upadhyaya, Paricha; Karki, Prahlad (Nepalese Heart Journal, 2022)
Background and Aims: Inflammation plays important role in atherosclerosis. Recently, neutrophil-to-lymphocyte ratio(NLR) has emerged as new inflammatory marker in identification of coronary artery disease(CAD). We aimed to evaluate correlation of NLR with CAD severity and propose suitable cut-off NLR for predicting CAD. Methods: This cross-sectional study included 147 patients undergoing coronary angiography for angina with ischemic ECG changes. CAD severity was assessed by SYNTAX score and categorized into low, intermediate and high SYNTAX group. Neutrophil and lymphocyte count determined by BeneSphera analyser and NLR was calculated. Statistical analysis was performed using chi-square, ANOVA, Pearson’s correlation test and logistic regression analysis. Results: In 147 patients [mean age 61.27±12.87year (25-86 years);68% male],NLR ranged from 1.0 to 9.66[median 2.53(1.96-3.73 IQR), mean 3.21±1.86].The NLR (mean ± SD) in low, intermediate and high SYNTAX group were 2.35±1.27, 3.04±1.54l, 4.72±2.07 respectively (p<0.0001).High SYNTAX group more frequently had diabetes mellitus, dyslipidemia, smoker, alcohol consumer, were older , and had significantly high neutrophil count, NLR values and low lymphocyte count. In univariate analysis, diabetes mellitus, NLR, neutrophil and lymphocyte count were predictors of high SYNTAX score. In the multiple logistic regression analysis, NLR >3[OR=17.36, 95% CI 6.7-44.5, p=0.001] was identified as independent predictor of high SYNTAX score. In ROC analysis, NLR ≥ 1.785 was best suitable cut-off to identify presence of CAD with sensitivity of 97.4% and specificity of 83.3%. Conclusion: NLR correlated positively with presence and severity of CAD as assessed by SYNTAX score